Being a Muslim in the World - Dabashi, H. author. aut Link
VIII, 166 p.
Keywords: What does it mean to be a Muslim - in this world, in this deeply transformative time? Hamid Dabashi suggests that the transition to a changed, post-Western world requires the crafting of a new language of critical conversation with Islam and its cosmopolitan heritage - a language that is tuned to the emerging, not the disappearing, world.